2001
DOI: 10.1142/s0217984901003172
|View full text |Cite
|
Sign up to set email alerts
|

Optical Doping of Nitrides by Ion Implantation

Abstract: A series of rare earth elements (RE) were implanted in GaN epilayers to study the lattice site location and optical activity. Rutherford backscattering spectrometry in the channeling mode(RBS/C) was used to follow the damage behavior in the Ga sublattice and the site location of the RE. For all the implanted elements (Ce, Pr, Dy, Er, and Lu) the results indicate the complete substitutionality on Ga sites after rapid thermal annealing at 1000 o C for 2 min. The only exception occurs for Eu that occupies a Ga di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…The widths of the Eu-and the Ga-scans are seen to be similar for both directions indicating that Eu is incorporated on substitutional Ga-sites. Eu is often seen to incorporate slightly displaced from the perfect Ga-site 14,15 ; however, in this case, due to the high minimum yield of the Eu scans, it is difficult to determine a value for this displacement. In fact, the fits shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The widths of the Eu-and the Ga-scans are seen to be similar for both directions indicating that Eu is incorporated on substitutional Ga-sites. Eu is often seen to incorporate slightly displaced from the perfect Ga-site 14,15 ; however, in this case, due to the high minimum yield of the Eu scans, it is difficult to determine a value for this displacement. In fact, the fits shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lattice constants of a pure GaN powder sample without Eu doping grown at 1000 ºC are found to be smaller (a = 3.186 Å and c = 5.178 Å) than those of sample no.6 grown at the same temperature with Eu doping. It is well known that the majority of the Eu 3+ ions occupy the substitutional Ga 3+ trivalent ionic states when incorporated in GaN [13]. Greater incorporation of Eu increases the lattice constants, as Eu is much bigger in size than Ga, with a corresponding increase in bond-length [14].…”
Section: Thementioning
confidence: 99%
“…Those who studied luminescence from samples implanted at varying doses [14,18,19,22,23,[49][50][51][52][53] generally found that implantations in the 1-5×10 15 cm −2 range gave stronger luminescence than lower doses. At higher fluences the inability to regrow a crystalline GaN layer from the amorphous state presents a limit.…”
Section: Optical Activationmentioning
confidence: 99%